Econometric Analysis of Food Crops’ Response to Climate Variability and Macroeconomic Policies’ Reforms in Nigeria (1978-2009) - O, Onoja Anthony; E. N, Ajie (Asian Journal of Agriculture and Rural Development, 2012)
This study investigated the extent to which climate variability (proxied by rainfall variability) and macroeconomic policies influenced food crop output in Nigeria. It used time series data obtained from Central Bank of Nigeria and National Bureau of Statistics (1978-2009). Four functional forms of OLS models were tried. The Cobb-Douglas function was finally adopted based on standard econometric model selection criteria and diagnosis. Chow test was used to test the hypotheses of the study. It was found that rainfall variability influenced crop output negatively. Climatic factor, loans guaranteed by Agricultural Credit Guarantee Scheme Fund and lending rate were all statistically significant drivers of crop output in the economy at p<0.05, p<0.01 and p<0.05 respectively. Their elasticities were respectively 4.01%, 0.52% and 0.98%. No structural difference between the economic reform era and the preceding era’s regression coefficients was found. Programmes to stem corruption and loan diversion; subsidization of agricultural credit and climate change adaptation capacity building programmes were recommended to bring about sustainable food security in the country.